4 Revising EMS dispatch procedures to manage growing demand in victoria, australia. (21st May 2017) - Andrew, E; Smith, Karen
Abstract : Aim: The Advanced Medical Priority Dispatch (AMPDS) system is used to triage emergency medical calls in Victoria, Australia. However, the level of response assigned to each AMPDS Event Type (ET), which may include triage away from an emergency medical service (EMS) attendance, is determined by Ambulance Victoria. This study aimed to increase the proportion of low-acuity calls diverted to secondary triage and onto an alternative service provider (ASP), ultimately reducing EMS demand. Methods: A review of the level of EMS response assigned to AMPDS ET was conducted using research, audit and clinical expertise. Existing 'time-critical' and 'acute but not time-critical' ETs were assessed for suitability against the assigned level of EMS response and existing dispatch rules. An analysis of events occurring pre-reform (8 Feb–8 May 2016) and post-reform (9 May–8 Aug 2016) was conducted. Results: A total of 105 'time-critical' ETs were assessed as suitable for downgrade to an 'acute' response, while 221 'acute' and 'time-critical' ETs were deemed suitable for diversion to secondary triage. The changes were implemented using staged approach, commencing in October 2015. The proportion of cases receiving a 'time-critical' EMS response decreased from 55.1% pre-reform to 48.9% post-reform (p<0.001).The proportion of emergency calls avoiding EMS dispatch increased from 8.8% pre-reform to 14.1% post-reform (p<0.001). Of the cases diverted to secondary triage post-reform, 32.4% were referred to an ASP, 30.2% were referred to a non-emergency transport service and 41.8% were returned for EMS dispatch. Conclusion: This study provides a sound methodological approach for revising EMS dispatch protocols. Ongoing monitoring of the dispatch changes aims to identify areas that may benefit from further optimisation. Conflict of interest: None declared. Funding: None declared.